Communication Between Ethnic Chinese and Indigenous People in the Retail Business - Daffa Fawwaz Rif’at; Kherudin Imawan (Riviera Publishing, 2025)
This study aims to analyze communication patterns between Chinese and indigenous retail business operators in the Cirebon area, and how interactions can influence cooperative relationships and business sustainability. The approach used in this study is qualitative, collecting data from several retail business operators in the Cirebon area. The theories applied in this study are Cross-Cultural Communication Theory and Business Communication Theory. The results indicate that cross-cultural communication in retail business is effective despite differences in language and culture, which do not hinder business operations. Business operators from the Chinese ethnic group tend to think long-term about the business, while indigenous people tend to focus on higher education. Challenges arising from cultural and language differences include differing perceptions between the two groups and a lack of effort in building business relationships. However, both groups demonstrate positive adaptation through open communication and mutual respect for each other's cultures and languages in business. This study underscores the importance of cross-cultural awareness in strengthening ethnic cooperation in the business world, particularly in the retail sector, which relies on direct and ongoing interaction. It also highlights the need for improved communication due to the linguistic and cultural differences between the two ethnic groups.